2011
DOI: 10.1111/j.1466-7657.2010.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

A framework to develop a clinical learning culture in health facilities: ideas from the literature

Abstract: Leadership, management and partnerships are pivotal for the creation and maintenance of positive learning environments. Diagnostic measurement tools can provide specific information about weaknesses across these areas. This knowledge can guide future initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 26 publications
(38 reference statements)
0
58
0
1
Order By: Relevance
“…These results agrees with several results which indicated that, although the importance of clinical teaching is universally acknowledge in the profession, little formal training is offered to prepare practitioners for this important role, and clinical practice setting that encourage teaching and learning can be powerful in educating both the existing nursing workforce and nursing students. [22,23] It is obvious from the present study that the nurses needs for theoretical knowledge and training skills were low. These results disagree with Hennessy et al (2006), who assess the training and development needs of nurses in Indonesia.…”
Section: Discussionmentioning
confidence: 93%
“…These results agrees with several results which indicated that, although the importance of clinical teaching is universally acknowledge in the profession, little formal training is offered to prepare practitioners for this important role, and clinical practice setting that encourage teaching and learning can be powerful in educating both the existing nursing workforce and nursing students. [22,23] It is obvious from the present study that the nurses needs for theoretical knowledge and training skills were low. These results disagree with Hennessy et al (2006), who assess the training and development needs of nurses in Indonesia.…”
Section: Discussionmentioning
confidence: 93%
“…[5] Thus, nursing educational environment encompasses both theoretical and clinical learning environments with subsequent impact and influence on the students' knowledge, practice, and attitude in addition to the whole educational process. [6,7] The grade point average (GPA) can be used as a reliable tool to measure the academic performance among nursing undergraduates. [8] Since nursing is a practice-based profession, the clinical field training is a vital component in the curricula of the undergraduate nursing education, and it allows nursing students to; integrate their cognitive, psychomotor and affective skills and correlate the theoretical part to real clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review on how to develop a clinical learning culture emphasizes the importance of role model attitudes and behaviors of the health care professionals [57]. Role modeling in spiritual care is a concept that is still theoretical in nature because of various reasons, such as feelings of incompetence to deliver spiritual care and secularization of the contemporary society.…”
Section: Integrating Theoretical Learning On Spiritual Care Into the mentioning
confidence: 99%